Effect of social integration on the establishment of health records among elderly migrants in China: a nationwide cross-sectional study - Chengchao Zhou; Zhengyue Jing; Lulu Ding; Xue Tang; Yuejing Feng (BMJ Open)
Objectives Essential public health service use among the migrants is the key obstacle of the equalisation of public health service in China. This study aims to investigate the status of the establishment of health records, and explore the effect of social integration on the establishment of health records among elderly migrants in China.Design and setting This is a cross-sectional study of data from the 2015 National Internal Migrants Dynamic Monitoring Survey in China.Participants and methods Respondents who not clear about whether they had established health records and who lived in the inflow area for less than 6 months were excluded. A total of 3158 migrants aged over 60 years were included in this study. Univariate logistic regression and multivariate logistic regression were employed to explore the association between social integration and establishment of health records.Results Approximately 41.6% of elderly migrants established health records in their inflow communities. Those elderly migrants from higher-income households were less likely to establish health records (p<0.001; OR=0.64; 0.51–0.80). Elderly migrants with local medical insurance (p<0.001; OR=2.03; 1.60–2.57), long-term settlement intention (p<0.001; OR=1.37; 1.15–1.63), and had more than three local friends (p<0.001; OR=1.54; 1.27–1.86) were more likely to establish health records.Conclusions This study demonstrates a relationship between social integration and establishment of the health records among elderly migrants in China. Improving the social integration of elderly migrants might be helpful to enhance the equalisation of essential public health services.